Destination Marketing and Management: Theories and Applications - Wang, Youcheng (CABI, 2014)
The development, marketing and management activities of destinations are very much in line with the development of the tourism industry at the global scale. Various sources have indicated that the tourism industry has the potential to keep growing for quite some time, driven by structural factors such as population growth, economic afﬂ uence, business expan- sion and age-related travel patterns, combined with social factors such as the globalization of cultures and electronic connectedness. As a result, hundreds of thousands of businesses, large and small, play their parts in selling and delivering services to those who travel to various destinations. However, destination marketing and management is a complex issue which requires a comprehensive, holistic and systematic approach to understand it. From the demand side, travellers have a variety of choices of available destinations; from the supply side, desti- nation marketing organizations at different levels are trying their best to compete for attention from a highly competitive marketplace. Therefore, destination competitiveness and attractive- ness demand effective and integrative marketing and management strategies which are based on a sound understanding of the market condition. This book offers a comprehensive understanding of the concept and scope of the tourism industry in general and of destination marketing and management in particular. Taking an integrated and comprehensive approach, it focuses on both the macro and micro aspects of destination marketing and management. Key themes and topics covered include the concept, scope and structure of destination marketing and management, destination planning and pol- icy, consumer decision-making processes, destination marketing research, destination brand- ing and positioning, destination product development and distribution, the role of emerging technologies in destination marketing, destination stakeholder management, destination safety, disaster and crisis management, destination competitiveness and sustainability, and challenges and opportunities for destination marketing and management.